Selenium deficiency-induced alterations in ion profiles in chicken muscle. - Haidong Yao; Xia Zhao; Ruifeng Fan; Hamid Sattar; Jinxin Zhao; Wenchao Zhao; Ziwei Zhang; Yufeng Li; Shiwen Xu (PLoS ONE)
Ion homeostasis plays important roles in development of metabolic diseases. In the present study, we examined the contents and distributions of 25 ions in chicken muscles following treatment with selenium (Se) deficiency for 25 days. The results revealed that in chicken muscles, the top ranked microelements were silicon (Si), iron (Fe), zinc (Zn), aluminum (Al), copper (Cu) and boron (B), showing low contents that varied from 292.89 ppb to 100.27 ppm. After Se deficiency treatment, essential microelements [Cu, chromium (Cr), vanadium (V) and manganese (Mn)], and toxic microelements [cadmium (Cd) and mercury (Hg)] became more concentrated (P < 0.05). Elements distribution images showed generalized accumulation of barium (Ba), cobalt (Co), Cu, Fe and V, while Cr, Mn, and Zn showed pin point accumulations in muscle sections. Thus, the ion profiles were generally influenced by Se deficiency, which suggested a possible role of Se deficiency in muscle dysfunctions caused by these altered ion profiles.